Feasibility and acceptability of digital student activity book (SAB) among primary schools in Selangor - Mello, Geraldine De; Md Razak, Mohamad Idham; Arumugam, Nalini; Bakri, Mohammed Hariri (Brooklyn Research and Publishing Institute, 2023)
The COVID-19 pandemic effects have been felt globally for the past three years. Physical separation was required, which hastened the education sector's digital revolution. Many countries throughout the world have experienced varied manifestations of Online Distance Learning (ODL) using digital Student Activity Book (SAB). In this study, we present a case study about the perceptions and experiences of teachers in relation to the adjustments made as a result of the pandemic conditions in primary schools in Selangor. It looked into the viability and acceptance of the digital Student Activity Book (SAB) in Selangor's elementary schools. A combination of quantitative and qualitative empirical data is used in this study. The conclusions show that SAB is a practical and well-liked educational tool for Selangor's primary school pupils.